Evaluating the Impact of STEM Academic Interventions on College Readiness for Rural Students - Janet B. Walton; Toni A. May; Carla C. Johnson (Trends in Higher Education, 2024)
This study used a quasi-experimental cohort approach to investigate the impact of early academic interventions on rural students’ academic college readiness as measured by indicators of science, mathematics, and English language proficiency in the United States. The program, delivered by a higher education institution, implemented a range of academic supports for students, including tutoring and in-class and after-school support by credentialed instructors, with the aim of preparing students for success in secondary and post-secondary educational experiences. The American College Testing (ACT) Aspire scores in science, mathematics, English language comprehension, and reading for a cohort of 8th-grade students in their second year of program participation (n = 100) were compared to the scores of a cohort of non-participants (n = 86) from the same school. Students who had participated in the program were significantly more likely than non-participants to meet college readiness benchmarks in all content areas and scored significantly higher than the non-program cohort in terms of their average percentile ranks. More research is needed to understand how particular interventions or combinations of interventions implemented in middle school impact students’ college readiness.